How to achieve impact from research - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel highlights how CGIAR Climate Security research translated into 12 major policy and operational outcomes across the Global South between 2023 and 2024. Examples include integrating climate security into Zambia’s Green Growth Strategy, supporting climate-resilient livelihoods for refugees with the World Food Programme in Jordan, informing UNHCR’s global efforts to protect people on the climate frontlines, and shaping Kenya’s national climate action plan. Together, these cases show how targeted research can move beyond analysis to influence policies and programs that address climate-related security risks in practice.